Effects of cusped field thruster on the performance of drag-free control system. (March 2018) - Cui, K.; Liu, H.; Jiang, W.J.; Sun, Q.Q.; Hu, P.; Yu, D.R.
Abstract: With increased measurement tasks of space science, more requirements for the spacecraft environment have been put forward. Those tasks (e.g. the measurement of Earth's steady state gravity field anomalies) lead to the desire for developing drag-free control. Higher requirements for the thruster performance are made due to the demand for the drag-free control system and real-time compensation for non-conservative forces. Those requirements for the propulsion system include wide continuous throttling ability, high resolution, rapid response, low noise and so on. As a promising candidate, the cusped field thruster has features such as the high working stability, the low erosion rate, a long lifetime and the simple structure, so that it is chosen as the thruster to be discussed in this paper. Firstly, the performance of a new cusped field thruster is tested and analyzed. Then a drag-free control scheme based on the cusped field thruster is designed to evaluate the performance of this thruster. Subsequently, the effects of the thrust resolution, transient response time and thrust uncertainty on the controller are calculated respectively. Finally, the performance of closed-loop system is analyzed, and the simulation results verify the feasibility of applying cusped field thruster to drag-free flight in the space science measurement tasks. Highlights: The dynamic performance of a cusped field thruster is tested and analyzed. A drag-free control system is designed to evaluate thruster performance. Effects of thruster performance parameters on whole system are compared. This thruster meets the requirements of drag-free flight in space science tasks.